(3eTcGI GdeUGHjMs - (3eMeO Hf YHO Gddg GdNWjH GdYeQj, CHh YHO Gddg, hdj GdOjf, GdJHQjRj , (B741 (3g` s ((3CHh GdHQcGJ eMjj GdOjf NhfO SYjO Hf Qcf GdOjf GdMSjf GdeYQha HGdQShd OGQs)
(3ChdgG (B:s
(3cJGH GdHjhY HGH GdcSH hWdH GdMdGd GdaUd GdChd (B: (3Yf GdeKOGe Hf jcQH bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3eG Ccd CMO WYGeG bW NjQG ef Cf jCcd ef Yed jOjg (B"s
(3BNQgG (B:s
(3GdaUd GdKGdK ef cJGH KhGH gPg GdCeI hGdMeO ddg QH GdYGdejfs
(3JGQjN GdGfJgGA ef GdJUfja (B: (3ThGd (B737 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 234s
(3eYLe GdeDdajf (B3 / 437s
(3cTa GdXfhf (B2 / 1699s
(3eYLe GdeWHhYGJ (B627s
Keywords: (3GdMOjK hGdeUWdMs